Cattle production under grazing with improved forages in the lowland tropics of Colombia - Sotelo Cabrera, Mauricio Efren; Gutiérrez Solís, Jhon Freddy; Peters, Michael; Hincapié Carvajal, Belisario; Burkart, Stefan (International Center for Tropical Agriculture, 2017)
* Increase in global population and changes in people’s lifestyles and diets generate high demand for animal protein sources. * Cattle production systems in Colombia are mostly extensive and inefficient. * The International Center for Tropical Agriculture (CIAT) works on sustainable intensification (SI) of livestock systems through improving their efficiency and productivity while mitigating negative environmental effects (e.g. deforestation, greenhouse gas emissions). * SI of livestock systems can be achieved through selection and breeding and subsequent adoption of improved forages, which can either be used as stand-alone technology or be part of a (e.g. silvopastoral) system. * Silvopastoral systems (SPS) have shown excellent results in terms of higher biomass production, higher animal stocking rates, better nutritional quality and positive environmental effects.